Artificial hybrid solid electrolyte layer modified lithium metal negative electrode constructed by gas-liquid mixed plasma in one step and preparation method and application of artificial hybrid solid electrolyte layer modified lithium metal negative electrode
The inorganic-organic hybrid solid electrolyte layer is constructed by gas-liquid mixed plasma, which solves the problems of lithium dendrites growth and volume effects in the application of lithium metal negative electrodes, and significantly improves the cycle stability and electrochemical performance of lithium metal batteries. .
Patent Information
- Application Number
- CN202411624260.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-18
AI Technical Summary
In practical applications, lithium metal negative electrodes face problems such as lithium dendrites growth, volume effect, low cycle life, interface instability, and corrosion of intermediate products, which seriously affect battery performance.
The artificial hybrid solid electrolyte layer is constructed in one step by using gas-liquid mixed plasma to modify the lithium metal negative electrode. Through the plasma equipment, nitrogen and dimethyl carbonate are used as a mixing source to construct an inorganic-organic hybrid solid electrolyte layer on the surface of the lithium metal.
Effectively alleviate volume changes during metal lithium deposition, inhibit the growth of lithium dendrites, improve the cyclic stability and electrochemical performance of lithium metal batteries, and enhance the stability and mechanical strength of the SEI layer.
Smart Images

Figure CN119480933A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium metal composite negative electrode materials, and in particular to a lithium metal negative electrode modified by constructing an artificial hybrid solid electrolyte layer in one step using gas-liquid mixed plasma, a preparation method thereof, and an application in a lithium metal negative electrode. Background Art
[0002] In recent years, people's demand for more advanced portable electronic devices has continued to grow, and lithium metal batteries are widely used as energy storage devices in various electronic devices. Compared with the most commonly used graphite anode material in commercial lithium-ion batteries, metal lithium (Li) anode has a higher theoretical capacity (3860mAh g -1 ), smaller mass density (0.534 g cm -3 ) and the lowest electrochemical potential, and is considered to be the ideal negative electrode material for future lithium batteries. However, lithium metal negative electrodes still face many problems in practical applications, such as lithium dendrite growth, volume effect, low cycle life, interface instability, intermediate product corrosion, etc. These problems have a serious negative impact on battery performance.
[0003] In the past few decades, with the rapid development of new material detection and characterization methods, researchers have adopted a variety of modification strategies to improve the stability of metal lithium negative electrodes, and artificial SEI layer construction is a common improvement strategy. Artificial SEI is mainly divided into organic SEI layer, inorganic SEI layer and organic / inorganic mixed SEI layer. For example, Chinese patent CN 202410624720.9 discloses an inorganic SEI layer rich in Al2O3; Chinese patent CN 202211442785.9 discloses an organic SEI layer rich in polysiloxane. However, a single inorganic SEI layer or organic SEI layer has shortcomings: the organic SEI layer does not have a large mechanical strength and cannot inhibit the growth of lithium dendrites; when faced with large volume changes of lithium metal, the inorganic SEI layer is brittle due to its large rigidity, which makes the SEI layer easy to break. Therefore, this patent proposes a new method to construct an organic / inorganic hybrid SEI layer, which has the advantages of both inorganic SEI layer and organic SEI layer: the organic SEI layer has good elasticity and can resist the volume effect of lithium metal; the inorganic SEI has high rigidity and mechanical strength and can effectively inhibit the growth of dendrites. In this way, the electrochemical performance of lithium metal batteries can be improved.
[0004] At present, the construction methods of artificial SEI layers have been developed in a variety of ways. A plasma chemically enhanced vapor deposition method (PECVD) has come into the field of vision of researchers. Plasma technology has been proven to be an effective way to construct artificial SEI. The plasma radicals formed by plasma technology can react with lithium to form a SEI layer with controllable composition. As disclosed in Chinese patent CN 202211557484.0, a SEI layer rich in organic complexes is constructed using liquid source PECVD technology. However, there are no reports on the application of PECVD to the preparation of an artificial SEI layer of organic / inorganic mixed components. Based on this, this patent proposes a method using a mixture of liquid source and gas source so that the artificial SEI layer is an organic / inorganic mixed component. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a lithium metal negative electrode modified by constructing an artificial hybrid solid electrolyte layer using a gas-liquid mixed plasma, in order to solve the problem of unstable interface of the existing lithium metal negative electrode, in order to address the problems of volume expansion and dendrite growth of lithium metal negative electrodes. The present invention uses a plasma device to prepare DMC&N2@Li negative electrode material in one step using nitrogen and dimethyl carbonate as mixed sources. The DMC&N2@Li negative electrode material of the present invention can effectively slow-release the volume change during the deposition of metallic lithium and inhibit the growth of lithium dendrites, has a high cycle stability, and can effectively improve the electrochemical performance of lithium metal batteries. It has broad application prospects and development prospects in the fields of mobile electronic devices, electric vehicles, aerospace, etc.
[0006] The technical solution of the present invention to solve the above technical problems is as follows:
[0007] A method for preparing a lithium metal negative electrode modified by constructing an artificial hybrid solid electrolyte layer in one step by gas-liquid mixed plasma is provided, comprising the following steps:
[0008] (1) encapsulating a metal lithium sheet into a quartz tube under a protective atmosphere and placing the tube in a plasma device;
[0009] (2) sequentially connecting the gas source, the liquid source device sealed with the liquid source, the quartz tube of step (1) and the vacuum pump, and connecting the copper rings at both ends of the plasma device to the radio frequency power supply;
[0010] (3) Turn on the vacuum pump to evacuate the plasma device with the quartz tube, and at the same time, the gas source introduces gas into the liquid source device in step (2); turn on the RF power switch of the plasma device, adjust the RF power, and after ignition, perform a plasma reaction to obtain an artificial hybrid solid electrolyte layer modified lithium metal negative electrode.
[0011] By adopting the technical solution, the present invention uses a gas and liquid mixed source as a plasma excitation source to form an artificial hybrid solid electrolyte layer on the surface of the metal negative electrode. The artificial hybrid solid electrolyte layer is an inorganic-organic hybrid solid electrolyte layer, which can effectively isolate lithium metal from direct contact with the electrolyte. The interface layer can realize the horizontal migration of lithium ions, achieve uniform deposition, and inhibit the growth of lithium dendrites. Therefore, the solid electrolyte layer constructed by solid and liquid mixed source plasma surface engineering has better electrochemical performance and safety.
[0012] Preferably, in step (2), the liquid source is dimethyl carbonate, more preferably dimethyl carbonate (DMC) at battery-grade concentration.
[0013] Preferably, in step (2), the gas source is nitrogen.
[0014] Preferably, in step (2), the plasma device consists of a quartz tube, a flange, and a copper ring.
[0015] Preferably, in step (3), the vacuum degree of the plasma device is 20 Pa.
[0016] Preferably, in step (3), the gas flow rate is 20 scc / min.
[0017] Preferably, in step (3), the radio frequency power is 50-100W, and more preferably, the radio frequency power is 80-100W.
[0018] Preferably, in step (3), the plasma reaction time is 10-60 s, and more preferably, the plasma reaction time is 30-60 s.
[0019] Preferably, the main components of the artificial hybrid solid electrolyte layer are Li3N, Li2O, and CH3OCO2Li.
[0020] Preferably, the protective atmosphere includes at least one of argon and helium.
[0021] The present invention also provides a lithium metal negative electrode prepared by the method of modifying the lithium metal negative electrode by one-step construction of an artificial hybrid solid electrolyte layer using any of the above-mentioned gas-liquid mixed plasmas.
[0022] The present invention also provides an application of a lithium metal negative electrode prepared by any of the above-mentioned methods of constructing an artificial hybrid solid electrolyte layer in one step using a gas-liquid mixed plasma to modify a lithium metal negative electrode in the battery field as a lithium metal negative electrode material for a lithium battery.
[0023] The present invention uses a one-step method of gas-liquid mixed plasma to quickly construct an inorganic-organic hybrid solid electrolyte layer on the surface of lithium metal. The organic-inorganic hybrid solid electrolyte layer can alleviate the volume change during the lithium metal deposition process and inhibit the growth of lithium dendrites. The modified lithium metal negative electrode can exhibit better electrochemical performance and safety, providing more possibilities and inspiration for the commercialization of lithium metal negative electrodes.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The gas-liquid mixed plasma method of constructing an artificial solid electrolyte layer in the present invention is to construct the liquid source DMC and the gas source nitrogen plasma on the surface of lithium metal in one step. The main components of the inorganic layer are lithium nitride and lithium oxide. + The migration barriers in lithium nitride and lithium oxide are 0.13 eV and 0.25 eV, respectively. Therefore, the inorganic layer can achieve Li + The rapid transmission of lithium nitride and lithium oxide can alleviate the growth of lithium dendrites. At the same time, the mixed interface of lithium nitride and lithium oxide has a better adsorption energy for lithium (-4.88eV), which can effectively reduce the interface impedance and increase the stability of the SEI layer interface. The main component of the organic layer is lithium methyl carbonate (LMC), which can effectively enhance the mechanical stability of the solid electrolyte layer and effectively resist the growth of lithium dendrites.
[0026] At the same time, the artificial hybrid inorganic-organic solid electrolyte layer can more effectively block lithium metal and electrolyte compared to the natural solid electrolyte layer, thereby reducing the side reactions between lithium metal and electrolyte.
[0027] The lithium metal negative electrode modified by the present invention has higher cycle performance, impedance performance, rate performance and coulombic efficiency than commercial electrodes. It can effectively improve the electrochemical performance of lithium metal batteries, provide possibilities for commercial lithium metal batteries, and have broad application prospects in mobile communications and new energy electric vehicles. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is the surface SEM image of Example 1;
[0029] Figure 2 A schematic diagram of the composition of the artificial SEI layer of the present invention;
[0030] Figure 3 It is a long cycle diagram of symmetrical batteries of Examples 1, 2, 3 and Comparative Examples 1, 2, 3;
[0031] Figure 4 It is a comparison diagram of the impedance before cycling of the symmetrical batteries of Examples 1, 2, 3 and Comparative Examples 1, 2, 3;
[0032] Figure 5The impedance comparison diagram of the symmetrical batteries of Examples 1, 2, 3 and Comparative Examples 1, 2, 3 after cycling. DETAILED DESCRIPTION
[0033] In order to better clarify and understand the purpose, process scheme and advantages of the present invention, the technical scheme and implementation method of the present invention are further described clearly, completely and in detail through specific examples and in combination with the accompanying drawings. It should be noted that the embodiments described in the present invention are implemented on the premise of the technical scheme of the present invention, and detailed implementation methods and specific operating processes are given, but they are only part of the embodiments of the present invention, not all of the embodiments. The specific implementation methods described are limited to explaining and interpreting the present invention, and do not limit the present invention. Based on the embodiments in the present invention, all other implementation methods obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0034] The experimental methods and conditions used in the embodiments of the present invention are conventional methods and conventional conditions unless otherwise specified. The materials, reagents or instruments used in the embodiments, unless otherwise specified, can be obtained from commercial sources or prepared by conventional methods. The reaction conditions embodied in the content of the invention of the present invention can achieve the reaction and obtain the product of the expected effect. Due to space limitations, some embodiments are listed below to further illustrate the advantages of the technical solution of the present invention.
[0035] Embodiment 1:
[0036] A method for preparing a lithium metal negative electrode modified by constructing an artificial hybrid solid electrolyte layer in one step using a gas-liquid mixed plasma, the preparation method comprising the following steps:
[0037] (1) Dimethyl carbonate (DMC) was placed in a liquid source device in an argon-filled glove box. At the same time, a commercial lithium sheet with a diameter of 15 mm, a thickness of 0.4 mm, and a purity of 99.9% (Tianjin Zhongneng Lithium Industry Co., Ltd.) was sealed in a quartz tube in an argon-filled glove box.
[0038] (2) Transfer the quartz tube outside the glove box. Then install the quartz tube into the plasma equipment. One end of the quartz tube is connected to the liquid phase device, and the other end is connected to the vacuum pump. The other end of the liquid phase device is connected to the nitrogen gas line.
[0039] (3) Then, the quartz tube is evacuated and nitrogen is introduced into the liquid phase device. Under the continuous vacuum action of the pump, the nitrogen and DMC vapor mixed atmosphere enters the quartz tube. Turn on the RF power switch of the plasma device, adjust the RF power to 100W, and control the vacuum degree in the device to 20Pa. The temperature is room temperature. When a pink glow appears inside the quartz tube, the nitrogen and DMC mixed plasma reacts with the lithium sheet to form a Li3N-Li2O-CH3OCO2Li inorganic-organic hybrid solid electrolyte interface layer (SEI). After reacting for 30s, turn off the RF power to obtain the DMC&N2@Li negative electrode.
[0040] Embodiment 2:
[0041] A method for preparing a lithium metal negative electrode modified by constructing an artificial hybrid solid electrolyte layer with gas-liquid mixed plasma, the preparation method comprising the following steps:
[0042] (1) Dimethyl carbonate (DMC) was placed in a liquid source device in an argon-filled glove box. At the same time, a commercial lithium sheet with a diameter of 15 mm, a thickness of 0.4 mm, and a purity of 99.9% (Tianjin Zhongneng Lithium Industry Co., Ltd.) was sealed in a quartz tube in an argon-filled glove box.
[0043] (2) Transfer the quartz tube outside the glove box. Then install the quartz tube into the plasma equipment. One end of the quartz tube is connected to the liquid phase device, and the other end is connected to the vacuum pump. The other end of the liquid phase device is connected to the nitrogen gas line.
[0044] (3) Then, the quartz tube is evacuated and nitrogen is introduced into the liquid phase device. Under the continuous vacuum action of the pump, the nitrogen and DMC vapor mixed atmosphere enters the quartz tube. Turn on the RF power switch of the plasma device, adjust the RF power to 90W, and control the vacuum degree in the device to 20Pa. The temperature is room temperature. When a pink glow appears inside the quartz tube, the nitrogen and DMC mixed plasma reacts with the lithium sheet to form a Li3N-Li2O-CH3OCO2Li inorganic-organic hybrid solid electrolyte interface layer (SEI). After reacting for 30s, turn off the RF power to obtain the DMC&N2@Li negative electrode.
[0045] Embodiment 3:
[0046] A method for preparing a lithium metal negative electrode modified by constructing an artificial hybrid solid electrolyte layer with gas-liquid mixed plasma, the preparation method comprising the following steps:
[0047] (1) Dimethyl carbonate (DMC) was placed in a liquid source device in an argon-filled glove box. At the same time, a commercial lithium sheet with a diameter of 15 mm, a thickness of 0.4 mm, and a purity of 99.9% (Tianjin Zhongneng Lithium Industry Co., Ltd.) was sealed in a quartz tube in an argon-filled glove box.
[0048] (2) Transfer the quartz tube outside the glove box. Then install the quartz tube into the plasma equipment. One end of the quartz tube is connected to the liquid phase device, and the other end is connected to the vacuum pump. The other end of the liquid phase device is connected to the nitrogen gas line.
[0049] (3) Then, the quartz tube is evacuated and nitrogen is introduced into the liquid phase device. Under the continuous vacuum action of the pump, the nitrogen and DMC vapor mixed atmosphere enters the quartz tube. Turn on the RF power switch of the plasma device, adjust the RF power to 80W, and control the vacuum degree in the device to 20Pa. The temperature is room temperature. When a pink glow appears inside the quartz tube, the nitrogen and DMC mixed plasma reacts with the lithium sheet to form a Li3N-Li2O-CH3OCO2Li inorganic-organic hybrid solid electrolyte interface layer (SEI). After reacting for 30s, turn off the RF power to obtain the DMC&N2@Li negative electrode.
[0050] Performance Testing
[0051] The lithium metal negative electrode materials prepared in the above Examples 1 to 3 were assembled into lithium-lithium symmetrical cells in an argon atmosphere glove box for electrochemical testing. The electrolyte was 1 mol / L LiTFSI / DOL:DEM (1:1 volume ratio, DOL: 1,3-dioxolane; DME: ethylene glycol dimethyl ether) with 1 wt% LiNO3 added, and the diaphragm was Celgard 2400. The battery was assembled in the order of positive electrode shell, lithium metal negative electrode material, electrolyte, diaphragm, lithium metal negative electrode material, and negative electrode shell, and sealed with a fully automatic packaging machine.
[0052] Preparation of comparative example 1:
[0053] A commercial lithium sheet with a diameter of 15 mm, a thickness of 0.4 mm, and a purity of 99.9% (Tianjin Zhongneng Lithium Industry Co., Ltd.) was selected as the lithium metal negative electrode, and a lithium-lithium symmetrical battery was assembled in an argon atmosphere glove box for electrochemical testing. The electrolyte was 1 mol / L LiTFSI / DOL:DEM (1:1 volume ratio, DOL: 1,3-dioxolane; DME: ethylene glycol dimethyl ether) with 1wt% LiNO3 added, and the diaphragm was Celgard 2400. The battery was assembled in the order of positive electrode shell, lithium metal negative electrode material, electrolyte, diaphragm, lithium metal negative electrode material, and negative electrode shell, and sealed with a fully automatic packaging machine.
[0054] Preparation of comparative example 2:
[0055] 1) In a glove box, a commercial lithium sheet with a diameter of 15 mm, a thickness of 0.4 mm, and a purity of 99.9% (Tianjin Zhongneng Lithium Industry Co., Ltd.) was sealed in a quartz tube.
[0056] (2) Transfer the quartz tube outside the glove box. Then install the quartz tube into the plasma equipment. One end of the quartz tube is connected to the nitrogen gas line, and the other end is connected to the vacuum pump.
[0057] (3) Then, the quartz tube is evacuated and nitrogen is introduced. As the pump continues to evacuate, nitrogen vapor enters the quartz tube. Turn on the RF power switch of the plasma device, adjust the RF power to 80W, and control the vacuum degree in the device to 20Pa. The temperature is room temperature. When a pink-orange-red glow appears inside the quartz tube, the nitrogen plasma reacts with the lithium sheet to form a Li3N inorganic solid electrolyte interface layer (SEI). After reacting for 30 seconds, turn off the RF power to obtain the N2@Li negative electrode.
[0058] (4) Assemble a lithium-lithium symmetric battery in an argon atmosphere glove box for electrochemical testing. The electrolyte is 1 mol / L LiTFSI / DOL:DEM (1:1 volume ratio, DOL: 1,3-dioxolane; DME: ethylene glycol dimethyl ether) with 1 wt% LiNO3 added, and the diaphragm is Celgard 2400. Assemble the battery in the order of positive electrode shell, lithium metal negative electrode material, electrolyte, diaphragm, lithium metal negative electrode material, and negative electrode shell, and press and seal it with a fully automatic packaging machine.
[0059] Production Comparative Example 3:
[0060] (1) Dimethyl carbonate (DMC) was placed in a liquid source device in an argon-filled glove box. At the same time, a commercial lithium sheet with a diameter of 15 mm, a thickness of 0.4 mm, and a purity of 99.9% (Tianjin Zhongneng Lithium Industry Co., Ltd.) was sealed in a quartz tube in an argon-filled glove box.
[0061] (2) The quartz tube is transferred outside the glove box. Then the quartz tube is installed in the plasma equipment. One end of the quartz tube is connected to the liquid phase device, and the other end is connected to the vacuum pump.
[0062] (3) Then, the quartz tube was evacuated, the RF power switch of the plasma device was turned on, the RF power was adjusted to 80W, and the vacuum degree in the device was controlled to be 20Pa. The temperature was room temperature. When a purple-red glow appeared inside the quartz tube, the DMC plasma reacted with the lithium sheet to form a Li2O-CH3OCO2Li inorganic-organic hybrid solid electrolyte interface (SEI). After reacting for 30s, the RF power was turned off to obtain the DMC@Li negative electrode.
[0063] (4) Assemble a lithium-lithium symmetric battery in an argon atmosphere glove box for electrochemical testing. The electrolyte is 1 mol / L LiTFSI / DOL:DEM (1:1 volume ratio, DOL: 1,3-dioxolane; DME: ethylene glycol dimethyl ether) with 1 wt% LiNO3 added, and the diaphragm is Celgard 2400. Assemble the battery in the order of positive electrode shell, lithium metal negative electrode material, electrolyte, diaphragm, lithium metal negative electrode material, and negative electrode shell, and press and seal it with a fully automatic packaging machine.
[0064] After the battery was stationary for 24 hours, electrochemical tests were performed on Examples 1-3 and Comparative Examples 1-3 using a Xinwei electrochemical workstation. The electrochemical tests were all performed at 30°C, mainly including constant current charge and discharge tests and electrochemical impedance analysis. 2 , capacity is 1 mAh / cm 2 The long cycle performance of the battery was tested under the conditions of 0.5, 1, 2, 5, 1 mA / cm 2 Current density, 1 mAh / cm 2 The rate performance of the battery was tested at a fixed capacity. 2 , capacity is 1 mAh / cm 2 After 100 cycles under the condition of , the electrochemical impedance was tested. The negative electrode materials of Examples 1-3 and Comparative Examples 1-3 were selected and paired with the copper positive electrode to make a lithium-copper battery. 2 , capacity is 1 mAh / cm 2 After 100 cycles under the conditions, the Coulomb efficiency was tested.
[0065] The performance test results are as follows:
[0066] 1. At 1mA / cm 2 Current density, 1mAh / cm 2 Under the capacity, the long cycle performance of the battery is tested.
[0067] The interfacial impedances of the batteries of Examples 1-3 and Comparative Examples 1-3 before cycling were 415Ω, 265Ω, 121Ω, 105Ω, 73Ω, and 41Ω, respectively; after 100 cycles, the interfacial impedances were reduced to 68Ω, 59Ω, 42Ω, 26Ω, 17Ω, and 6Ω.
[0068] 2. At 0.5, 1, 2, 5, 1 mA / cm 2 Current density, 1 mAh / cm 2 The battery rate performance is tested at a fixed capacity.
[0069] The overpotentials of the cells in Comparative Example 1 were 24.4, 29.8, 59.8, and 94.2 mV, respectively;
[0070] The cell overpotentials of Comparative Example 2 were 23.4, 29.4, 57.8, and 94.0 mV, respectively;
[0071] The battery overpotentials of Comparative Example 3 are 22.1, 27.6, 57.5 and 92.2 mV respectively.
[0072] The overpotentials of the cell in Example 1 were 19.4, 25.6, 45.1, and 84.3 mV, respectively;
[0073] The overpotentials of the battery in Example 2 were 15.4, 23.7, 41.9, and 75.5 mV, respectively;
[0074] The battery of Example 3 exhibits the smallest overpotentials, which are 13.1, 22.2, 37.8 and 60.7 mV, respectively, indicating better rate performance.
[0075] 3. At 1mA / cm 2 Current density, 1mAh / cm 2 When charging and discharging at capacity, the stable overpotentials of the batteries of Examples 1 and 2 are 18.3 mV and 15.3 mV, respectively, and obvious overpotential fluctuations occur after 385 h and 567 h of cycling. The stable overpotentials of the batteries of Example 3 are 11.5 mV, respectively, and no overpotential fluctuations occur after 900 h of cycling. The stable overpotentials of the batteries of Comparative Examples 1, 2, and 3 are 24.2 mV, 23.0 mV, and 21.9 mV, respectively, and obvious overpotential fluctuations occur after 163 h, 175 h, and 322 h of cycling.
[0076] 4. At 1mA / cm 2 Current density, 1mAh / cm 2 When charged and discharged at the same capacity, the coulombic efficiency of the batteries of Examples 1 and 2 is 98.4% and 99.3%, respectively. The coulombic efficiency of the battery of Example 3 is 99.7%, and the coulombic efficiency of the batteries of Comparative Examples 1, 2, and 3 is 96.4%, 96.9%, and 97.5%, respectively.
[0077] Table 1 Summary of battery performance of Examples 1-3 and Comparative Examples 1-3
[0078]
[0079] From the above, it can be seen that the introduction of Li3N-Li2O-CH3OCO2Li inorganic-organic hybrid solid electrolyte interface layer can accelerate the Li +The DMC&N2@Li negative electrode material of the present invention has good cycle stability and has broad application prospects and development prospects in the fields of mobile electronic devices, electric vehicles, aerospace, etc.
[0080] The above-described embodiments are only preferred solutions of the present invention and are not intended to limit the present invention in any form. Other variations and modifications are possible without exceeding the technical solutions described in the claims.
Claims
1. A method for preparing a lithium metal negative electrode modified by constructing an artificial hybrid solid electrolyte layer in one step using a gas-liquid mixed plasma, characterized in that: The following steps are involved: (1) encapsulating a metal lithium sheet into a quartz tube under a protective atmosphere and placing the tube in a plasma device; (2) sequentially connecting a gas source, a liquid source device containing a sealed liquid source, a quartz tube, and a vacuum pump; (3) Turn on the vacuum pump to evacuate the plasma device with the quartz tube, and at the same time, introduce gas into the liquid source device; turn on the RF power switch of the plasma device, adjust the RF power, and after ignition, perform a plasma reaction to obtain an artificial hybrid solid electrolyte layer modified lithium metal negative electrode.
2. The method for preparing a lithium metal negative electrode modified by constructing an artificial hybrid solid electrolyte layer in one step by gas-liquid mixed plasma according to claim 1, characterized in that: In step (2), the liquid source is dimethyl carbonate.
3. The method for preparing a lithium metal negative electrode modified by constructing an artificial hybrid solid electrolyte layer in one step by gas-liquid mixed plasma according to claim 1, characterized in that: In step (2), the gas source is nitrogen.
4. The method for preparing a lithium metal negative electrode modified by constructing an artificial hybrid solid electrolyte layer in one step by gas-liquid mixed plasma according to claim 1, characterized in that: In step (3), the vacuum degree of the plasma device is 20 Pa.
5. The method for preparing a lithium metal negative electrode modified by constructing an artificial hybrid solid electrolyte layer in one step by gas-liquid mixed plasma according to claim 1, characterized in that: In step (3), the gas flow rate is 20 scc / min.
6. The method for preparing a lithium metal negative electrode modified by constructing an artificial hybrid solid electrolyte layer in one step by gas-liquid mixed plasma according to claim 1, characterized in that: In step (3), the radio frequency power is 50-100w.
7. The method for preparing a lithium metal negative electrode modified by constructing an artificial hybrid solid electrolyte layer in one step by gas-liquid mixed plasma according to claim 6, characterized in that: The radio frequency power is 80-100w.
8. The method for preparing a lithium metal negative electrode modified by constructing an artificial hybrid solid electrolyte layer in one step by gas-liquid mixed plasma according to claim 1, characterized in that: In step (3), the plasma reaction time is 10-60s.
9. A gas-liquid mixed plasma one-step constructed artificial hybrid solid electrolyte layer modified lithium metal negative electrode obtained by the preparation method of the gas-liquid mixed plasma one-step constructed artificial hybrid solid electrolyte layer modified lithium metal negative electrode according to any one of claims 1 to 8.
10. Application of the gas-liquid mixed plasma one-step construction of an artificial hybrid solid electrolyte layer to modify lithium metal negative electrode in the battery field according to claim 9.
Citation Information
Patent Citations
Ultrathin lithium film complex and preparation method thereof
CN113363456A
Plasma in-situ generated nitride layer composite lithium and preparation method and application thereof
CN116344749A
Gradient interface modified electrode material and preparation method and application thereof
CN118398759A